Ionospheric disturbances induced by a missile launched from North Korea on 12 December 2012. Issue 8 (29th August 2013) - Kakinami, Yoshihiro; Yamamoto, Masayuki; Chen, Chia‐Hung; Watanabe, Shigeto; Lin, Charles; Liu, Jenn‐Yanq; Habu, Hiroto
Abstract: [1] Ionospheric disturbances caused by a missile launched from North Korea on 12 December 2012 were investigated by using the GPS total electron content (TEC). The spatial characteristic of the front edge of V‐shaped disturbances produced by missiles and rockets was first determined. Considering the launch direction and the height of estimated ionospheric points at which GPS radio signal pierces the ionosphere, the missile passed through the ionosphere at heights of 391, 425, and 435 km at 0056:30, 0057:00, and 0057:30 UT, respectively. The observed velocities of the missile were 2.8 and 3.2 km/s at that time, which was estimated from the traveling speed of the front edge of V‐shaped disturbances. Westward and eastward V‐shaped disturbances propagated at 1.8–2.6 km/s. The phase velocities of the westward and eastward V‐shaped disturbances were much faster than the speed of acoustic waves reported in previous studies, suggesting that sources other than acoustic waves may have played an important role. Furthermore, the plasma density depletion that is often observed following missile and rocket launches was not found. This suggests that the depletion resulting from the missile's exhaust was not strong enough to be observed in the TEC distribution in the topside ionosphere. Key Points: Clear V‐shaped disturbance related a missile was found in GPS TEC The disturbance propagated faster than acoustic wave Plasma depletion was not found along the trajectory